Hubungan Tingkat Kecemasan Dengan Tingkat Kemandirian Activity of Daily Living Lansia Terlantar - Safitri, Intan; Hanafi Rochman, Uut; Esterilita, Mari (NHM PRESS, 2024)
The elderly population in Indonesia continues to increase, presenting challenges in health and well-being, including anxiety and independence in daily activities. This study aims to analyze the relationship between anxiety levels and independence in Activities of Daily Living (ADL) among neglected elderly individuals at the Budi Mulia 1 Social Welfare Home in East Jakarta. A quantitative approach was used, involving 153 neglected elderly participants. Data were collected through a questionnaire measuring anxiety with the Geriatric Anxiety Inventory (GAI) and ADL independence using the Barthel Index. Data analysis was conducted using SPSS software to examine the relationship between the two variables. The results showed that the majority of the elderly experienced moderate anxiety (71.9%) and mild dependence in ADL (55.6%). Hypothesis testing indicated a significant relationship between anxiety levels and ADL independence, with a p-value of 0.009 and a negative correlation coefficient (r = -0.210). There is a significant relationship between anxiety levels and ADL independence among neglected elderly individuals. Higher anxiety is associated with lower independence in daily activities. Interventions focused on reducing anxiety and enhancing social support and environmental conditions may help improve the independence and quality of life for the elderly.